Web Information Systems - WISE 2006 Workshops WISE 2006 International Workshops, Wuhan, China, October 23-26, 2006, Proceedings - Feng, Ling; Wang, Guoren; Zeng, Cheng; Huang, Ruhua (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2006)
This book constitutes the joint refereed proceedings of the three workshops held in conjunction with the 7th International Conference on Web Information Systems, WISE 2006, in Wuhan, China, in October 2006. A total of 90 papers were submitted to the three workshops, and 31 revised full papers were carefully selected for presentation. The Workshop on Web Information Access and Digital Library (WIADL 2006) - which aims at improving and facilitating Web information access by using digital libraries - included 14 out of 41 submissions. The Workshop of Web-Based Massive Data Processing (WMDP 2006) accounted for 13 papers, from 39 papers submitted. It discusses how to effectively and efficiently collect, extract, store, index, query and analyze massive data that has been accumulated in many web-based applications such as deep Web applications and Web search engines. The Workshop on Advances in Web-based Learning included 4 presentations selected from 10 submissions. New ideas on Web-based learning are presented - using the Web to access vast amount of information and resources - that allow implementing a range of new teaching and learning practices.